Analysis of the terms of development of infectious complications in patients after osteosynthesis of long bones - P.V. Tanasienko; H.B. Kolov; V.M. Tsokalo (Medičnì Perspektivi)
Determination of the influence of the timing of infectious complications in patients after osteosynthesis of long bones and its influence on the course of the infectious process. An analysis of the treatment of 207 patients with infectious complications after osteosynthesis of long bones, who were treated at the "Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine" from 2013 to 2017 was made. The first group included 148 patients who developed infectious complications after osteosynthesis of long bones with a plate. The second group included 59 patients who developed infectious complications after osteosynthesis of long bones with a blocking intramedullary rod. In 51.5% of patients of the first group after closed fractures, infectious complications were detected in the first 6 weeks after surgery. In 43.7% of patients of this group, manifestations of the inflammatory process occurred in the period from 6 weeks to 1 year. In 4.9% of patients of the first group, the infectious process (in the form of a fistula) did not occur acutely, but after one year after osteosynthesis. In 62.2% of patients after osteosynthesis as a result of an open fracture, the first manifestations of the infectious process appeared in the first 6 weeks after the operation. In 35.6% of patients of this cohort, the infectious process occurred within 6 weeks to 1 year after the surgical intervention. In 43.2% of patients of the second group, the first manifestations of infection began immediately after the operation in the form of non-healing of the postoperative wound, and in another 24.3% – in the first 6 weeks after the intervention. In 32.4% of patients in this cohort, an infectious process occurred more than a year after the intervention against the background of a consolidated fracture and a stable fixator. After BIOS with rod as a result of open fractures, in 72.7% of patients, the infectious process began immediately after the operation in the form of non-healing of the postoperative wound, and in another 27.3% – in the first 6 weeks after the intervention. The terms of the infection after osteosynthesis and its type reliably affect the development of complications in the injured person and have an indirect effect on their development. The structure of infectious complications is different depending on the time of occurrence and the type of osteosynthesis used to treat patients. In all observation groups, the infectious process localized in the tibia, which has both anatomical reasons and reasons related to the blood supply of this segment, was detected the most often.